Health Spending and Decentralization in Indonesia - Ioana Kruse; Menno Pradhan; Robert Sparrow (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2009)
Using a panel dataset of 320 Indonesian districts we examine the impact of district budgets on public health spending, utilization patters in the public and private sector, and private health spending in the four years after decentralization. We exploit the panel structure of the data and the fact that district budgets are largely driven by central government transfers to determine causal patterns. We find that the elasticity of public health spending with respect to district budgets is around 0.9 with a higher elasticity for development spending than for routine spending. District splits reduce public health spending. We find a positive effect of public district health spending on public sector utilization, with the strongest effects in the poorest two quintiles. We find no significant effects on private sector utilization and out of pocket health expenditures.
Keywords: 330; public spending; health; decentralization